Polymorphisms of the LEP, LEPR and HTR2C gene: obesity and BMI change in patients using antipsychotic medication in a naturalistic setting. (June 2011) - Gregoor, Jochem G; Weide, Jan van der; Loovers, Harriëët M; van Megen, Harold JGM; Egberts, Toine CG; Heerdink, Eibert R
Weight gain is a frequently occurring serious somatic adverse effect of atypical antipsychotic agents. Genetic factors influence the risk of an individual to gain weight.Objectives: To determine whether LEPR Q223R, LEP -2548G/A and HTR2C -759C/T polymorphisms are associated with obesity and weight change in patients using atypical antipsychotic drugs.Methods: A longitudinal study design was used in a naturalistic setting. The study population included 141 patients, all of whom were using an atypical antipsychotic drug. The body mass index was measured twice. Primary outcome measures were obesity at the moment of first measurement and body mass index change during treatment. Determinants were the LEPR Q223R (rs1137101), the LEP -2548G/A SNP (rs7799039) and the HTR2C -759C/T (rs3813929) polymorphisms.Results: Of the 141 included patients, 35 (24.8%) were obese. In females, presence of the LEPR 223R allele was associated with an increased risk of obesity (47.6 vs 17.6%; p = 0.03). In males this association was not found. None of the SNPs were significantly associated with weight change during treatment. Conclusions: The LEPR Q223R polymorphism may be a risk factor for obesity in women with a psychotic disorder treated with atypical antipsychotic drugs. This is in line with earlier findings of our group. Original submitted 18 May 2010; Revised submitted 14 February 2011